The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019 53rd Asilomar Conference on Signals, Systems, and Computers 2019
DOI: 10.1109/ieeeconf44664.2019.9048671
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Musculoskeletal Image Analysis

Abstract: The diagnosis, prognosis, and treatment of patients with musculoskeletal (MSK) disorders require radiology imaging (using computed tomography, magnetic resonance imaging (MRI), and ultrasound) and their precise analysis by expert radiologists. Radiology scans can also help assessment of metabolic health, aging, and diabetes. This study presents how machine learning, specifically deep learning methods, can be used for rapid and accurate image analysis of MRI scans, an unmet clinical need in MSK radiology. As a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The ECG is a one-dimensional (1-D) signal representing a time series, which can be analyzed using machine learning techniques for automated detection of certain abnormalities. Recently, deep learning techniques have been developed, which provide significant performance in radiological image analysis [4,5]. Convolutional neural networks (CNNs) have recently been shown to work for multi-dimensional (1-D, 2-D, and in certain cases, 3-D) inputs but were initially developed for problems dealing with images represented as two-dimensional inputs [6].…”
Section: Introductionmentioning
confidence: 99%
“…The ECG is a one-dimensional (1-D) signal representing a time series, which can be analyzed using machine learning techniques for automated detection of certain abnormalities. Recently, deep learning techniques have been developed, which provide significant performance in radiological image analysis [4,5]. Convolutional neural networks (CNNs) have recently been shown to work for multi-dimensional (1-D, 2-D, and in certain cases, 3-D) inputs but were initially developed for problems dealing with images represented as two-dimensional inputs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the study did not classify the complete, partial tears of ACL. The study Irmakci et al [ 41 ] was where the average AUC 0.878, 0.857 and 0.859 of models of three classes for AlexNet, ResNet-18 and GoogleNet 0.859 respectively. The one of the state work Tsai et al, 2020 [ 42 ] was used EfficientNet which is optimized and in the case of MRNet the AUC was 0.960, but on the knee, MRI AUC was 0.913 due to imbalanced classes.…”
Section: Discussionmentioning
confidence: 99%
“…The study of [ 40 ] related arthroscopy findings of MRI dataset and used DenseNet architecture upon 489 MRI samples only, in which 163 were from an ACL tear and 245 were from an intact ACL. The comparison study related to musculoskeletal Irmakci et al [ 41 ] performed three CNN architectures AlexNet, ResNet and GoogleNet, that achieved AUC 0.938, 0.956 and 0.890, respectively, detecting ACL tears on MRNet dataset. The ResNet-18 model was found better in the case of an ACL tear, but in the case of abnormalities, the ResNet result was not good.…”
Section: Related Workmentioning
confidence: 99%
“…Two other studies evaluated DL algorithms for meniscus tear detection using the publicly available "MRNet" data set [11]. For meniscus tear detection without differentiating laterality, one study using various CNNs achieved sensitivities of 62-69% and specificities of 76-81% [17]. The other study's CNN achieved a sensitivity of 86% and specificity of 89% by reportedly using coronal T1-weighted MR images only, which, however, are least accurate for radiologists to diagnose meniscal tears [15].…”
Section: Meniscus Tearsmentioning
confidence: 99%
“…Several additional studies using variations of publicly available and custom architecture CNNs reported sensitivities and specificities between 85 and 95% [15][16][17]. Table 1 summarizes key characteristics and performance levels of a group of representative studies.…”
Section: Introductionmentioning
confidence: 99%